Work in Progress on the Creation of the Three-Stringed Kulcapi - Panji Suroso; Uyuni Widiastuti; Rahmat Riswan Aidil Syahputra Siregar; Adina S Sembiring; Obed Sembiring; Ewin Johan Sembiring (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
This research tittle ‘work in progress on the creation of the three-stringed kulcapi’ wanted to examine how the work process of the creation of the kulcapi music instrument and can be explained descriptively. The kulcapi musical instrument which is considered to still have limitations in terms of producing its notes, and only having 2 strings, seems to be the cause of the less than optimal function in exploring the notes. In addition, the form of the kulcapi instrument is seen to be still very plain and very simple, this is felt to be one of the issues that must be overcome to be able to explore the kulcapi musical instrument to be more functional, both in producing tones and adding aesthetic value to the form of the kulcapi music instrument. In this research, a qualitative descriptive method is used. The process of tracing data and information is done diachronically to find out in full and complete about the kulcapi music instrument. The data collected comes from two sources, they are primary and secondary data. Primary data obtained through in-depth interviews and participant observation that aims to collect data followed by focus group discussions. This research produces findings including: a) The creation of three-stringed kulcapi instruments has a wider range of tone areas. b) can be functioned more flexible and can be explored in playing pentatonic and diatonic tones. c) The shape has the characteristic of the Karo people with the presence of ethnic Karo ornaments on the kulcapi’s body.